Experimental Characterization of Viscoelastic Behaviors of Nano-TiO2/CaCO3 Modified Asphalt and Asphalt Mixture - Chunli Wu; Liding Li; Wensheng Wang; Zhengwei Gu (Nanomaterials, 2021)
The purpose of this paper is to promote the application of nano-TiO2/CaCO3 in bituminous materials and present an experimental characterization of viscoelastic behaviors of bitumen and bituminous mixture modified by nano-TiO2/CaCO3. In this work, a series of viscoelastic behavior characterization tests were conducted, including dynamic shear rheometer (DSR) test for bitumen, uniaxial static compression creep test and dynamic modulus test for bituminous mixture. Moreover, various viscoelastic models with clear physical meanings were used to evaluate the influence of nano-TiO2/CaCO3 on the macroscopic performance of bitumen and bituminous mixture. The results show that bitumen and its mixtures are time-temperature dependent. The Christensen-Anderson-Marasteanu (CAM) model of frequency sweep based on DSR test indicated that adding nano-TiO2/CaCO3 can effectively capture the sensitivity of temperature. In addition, the incorporation of nano-TiO2/CaCO3 in bituminous mixture can significantly enhance the high-temperature anti-rutting, and slightly improve the low-temperature anti-cracking as well. At the same time, the modified Burgers model can accurately describe the viscoelastic behavior of bituminous mixtures in the first two creep stages, reflecting the consolidation effect of bituminous mixture. Also, the generalized Sigmoidal model can accurately grasp the characteristics of the relationship between dynamic modulus and reduced frequency and achieve good prediction effects in a wider frequency range.